Internalisasi Nilai-Nilai Pendidikan Islam melalui Habbit Forming (Pembiasaan) di SD Negeri 1 Candi Karanganyar - Agustina, Elda Ajizatul; Eliyanto, Eliyanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The aim of this research is to find out the Habbit Forming (Habitation) program at SD Negeri 1 Candi Karanganyar, the process of internalizing the values ​​of Islamic education at SD Negeri 1 Candi Karanganyar, and to find out the obstacles that occur in the process of internalizing the values ​​of Islamic education through Habbit Forming (habituation). at SD Negeri 1 Candi Karanganyar and the solutions taken to overcome it.This research is a type of qualitative research. Data collection methods use observation, interviews and documentation. Data analysis is carried out by reducing the data, presenting the data, then drawing conclusions. The results of the research show that there are various habituation activities which in their activities instill 3 values ​​of Islamic education that are formed in students, including the values ​​of faith, the values ​​of worship and the values ​​of morals. (1) Habits consist of annual, weekly, monthly, daily and spontaneous habits. (2) The internalization of the values ​​of Islamic education at SD Negeri 1 Candi is contained in the habituation activities carried out, and is divided into 3 values, namely the values ​​of faith, worship and morals, in each of which there are several habituation activities and different stages of internalization. (3) There are 3 obstacles that occur, namely age, time and place, solutions have been found for all three which can be used as evaluations to improve habits in the future. The success of internalizing the values ​​of Islamic education through familiarization at SD Negeri 1 Candi Karanganyar has been successful, the values ​​of Islamic education are slowly being accepted by students well.